2010
DOI: 10.1093/humrep/deq194
|View full text |Cite
|
Sign up to set email alerts
|

Increasing openness in oocyte donation families regarding disclosure over 15 years

Abstract: Parents with young OD children are clearly more inclined to disclosure compared with parents with older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 27 publications
3
34
1
10
Order By: Relevance
“…The emphasis on disclosure, and on early disclosure in particular, is reinforced in respondents' advice to other parents of a donor-conceived child. Despite the possibility that parents favoring disclosure might be over-represented in this survey, these findings are consistent with other studies reporting high levels of both actual and intended disclosure among parents of children conceived following oocyte donation (Söderström-Anttila et al, 2010;Readings et al, 2011). However, although children were aged under five years in more than 80% of cases where parents had already told their child, 90% of children who had not been told because they were deemed to be "too young" were also aged under 5 years.…”
Section: Disclosure Vs Non-disclosuresupporting
confidence: 91%
See 2 more Smart Citations
“…The emphasis on disclosure, and on early disclosure in particular, is reinforced in respondents' advice to other parents of a donor-conceived child. Despite the possibility that parents favoring disclosure might be over-represented in this survey, these findings are consistent with other studies reporting high levels of both actual and intended disclosure among parents of children conceived following oocyte donation (Söderström-Anttila et al, 2010;Readings et al, 2011). However, although children were aged under five years in more than 80% of cases where parents had already told their child, 90% of children who had not been told because they were deemed to be "too young" were also aged under 5 years.…”
Section: Disclosure Vs Non-disclosuresupporting
confidence: 91%
“…A number of studies undertaken in various countries have explored parents' views regarding disclosure to their donor-conceived children of the means of their conception. To date, most of the study populations relating to oocyte donation have been recipients of anonymous donation whose children have been aged up to eight years (Pettee and Weckstein, 1993;Weil et al, 1994;Söderström-Anttila et al, 1998;Baetens et al, 2000;Hahn and CraftRosenberg, 2002;Greenfeld and Klock, 2004;Klock and Greenfeld, 2004;Golombok et al, 2004Murray et al, 2006;Mac Dougall et al, 2007;van Berkel et al, 2007;Laruelle et al, 2012), although one recent Finnish study has included parents of children aged up to 14 years (Söderström-Anttila et al, 2010). These studies have revealed intended disclosure rates of between 26 and 81%, although not all parents indicating an intention to disclose will necessarily do so Golombok et al, 2006;Murray et al, 2006;Mac Dougall et al, 2007;van Berkel et al, 2007), and only three studies have included longitudinal data tracking parental disclosure behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the fertility clinics" psychosocial work-up prior to donation treatment include discussion of specific aspects of donation parenthood, the clinics" responsibility usually ends when the treatment succeeds. In Finland, a support group for gamete donation families was founded in 2009 as a consequence of the parents" wish for support and guidance both before treatment and after the birth of a donor offspring (Söderström-Anttila, et al, 2010). Another possibility is to incorporate support to gamete donation families within general child health care services, although this may entail that individual staff members have limited professional experience of donation families and may have opinions that are not entirely in line with national legislation (Sydsjo, Lampic, Sunnerud, & Svanberg, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although disclosing the details of the child's conception is becoming more common, a significant number of parents delay the intention of disclosing or decide not to tell their child at all [11][12][13] . In cases of anonymous donation, one of the reasons mentioned is the fact that the child cannot obtain any identifying information about the donor anyway 14,15 . One found that a half of the parents who chose anonymous donation, had done so to maintain confidentiality 16 .…”
Section: Introductionmentioning
confidence: 99%